Strategi Peningkatan Kemampuan Berfikir Kritis Siswa Melalui Learning Community - Mardliyah, Shibi Zuharoul; Salsabilla, Adelia Putri; Herianingtyas, Nur Luthfi Rizqa (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to describe the results of research on learning community strategies in improving students' critical thinking skills. The method used is a literature study that collects several previous studies to answer critical thinking, learning communities, and the influence of learning community methods in improving students' critical thinking skills. Critical thinking is a person's ability to reflect, re-examine, and modify existing thoughts. Learning community is interaction between students and students and students with teachers interactively. Previous research has mentioned that learning communities can make students interactive in learning. Based on the literature review conducted, it can be concluded that the learning community has a significant role in improving students' critical thinking skills.